Regeneração óssea vertical usando barreira não-porosa de politetrafluoretileno em implantes osteointegrados inseridos parcialmente na tíbia de coelhos - Macedo, Nelson Luiz de [UNESP] (1999)
The purpose of this study was to evaluate the possibility to obtaining guided bone regeneration utilizing a nonporous PTFE barrier in the osseointegrated implants, protruding from the bone level of the rabbit tíbia. The histologic characteristics of the interface between titanium implants, one group titanium-plasma coated, another group with acid-treated surfaces and the regenerated bone were also studied Twenty Screw-Vent implants were placed in tibias of five rabbits, two at the right side and two at the left side, protruding 3 mm from the bone level, to create a horizontal bone defect. ln the experimental side, the implants and adjacent bone were protected with a nonporous PTFE barrier. Histologic analysis after three months showed that all implants were in direct contact with the bane. Histologic measurements showed an average gain in bone height of the 2.15 and 2.42 mm for the barrier group and 1.95 and 0.43 mm for the control defects, in the titanium plasma-spray and acid-treated implant surfaces, respectively. The results suggest that the placement of implants protruding 3 mm from crestal bone defects may result in vertical bone augmentation and the regenerated bone is able to osseointegrate implants. lt seems to be critical the use of the PTFE barrier when acid-treated surface implants are inserted